Ph.D A quantitative summary of compliance with the 2030 Agenda in the European Union. Short title: 2030 agenda compliance in the EU - Onrubia Fernández, Jorge; Plaza Iniesta, Rocío; Sánchez Fuentes, Antonio Jesús (Papeles de Europa, 2022)
Successive to the Millennium Development Goals initiated in 2000, the 2030 Agenda for Sustainable Development approved in 2015 by the United Nations affects many of the political decisions currently being made. Through this Agenda, countries commit to taking actions aimed at 17 goals, 169 targets and 232 indicators created by the UN to measure them in terms of performance. Parallel to the creation of global objectives by the UN, Eurostat established 100 indicators (many equal or similar to those of the UN) focused on the countries of the European Union to monitor their development with respect to the 2030 Agenda.This work proposes to undertake an exhaustive analysis of the strengths and weaknesses of the European Union countries with respect to these set objectives, also analyzing the convergence or divergence among EU member states. To this end, we build partial synthetic indices for each goal, taking existing information on the indicators collected by Eurostat in order to combine these into a composite index that provides a global vision of the (relative) situation of each country in the EU region.
Keywords: 2030 Agenda; Eurostat; synthetic indices; European Union